SGLT-2 inhibitors on prognosis and health-related quality of life in patients with heart failure and preserved ejection fraction: A systematic review and meta-analysis - Yang, Danning; Zhang, Yu; Yan, Jie; Liu, Ming; An, Fengshuang (Frontiers in Cardiovascular Medicine, 2022)
Background Heart failure with preserved ejection fraction (HFpEF) is becoming the main subtype of heart failure, but lacks proven effective therapies. Sodium-glucose cotransporter-2 (SGLT-2) inhibitor, a new kind of oral glucose-lowering agent, shows a great effect on improving cardiovascular outcomes. Based on the results of current RCTs, we perform this meta-analysis to illustrate the therapeutic impact of SGLT2i in HFpEF patients. Methods We systematically searched the online database and 10 RCTs were involved. The primary outcome was the prognosis outcome of HFpEF patients, including a composite outcome of cardiovascular (CV) death and hospitalization for heart failure (HHF), CV mortality, HHF, and all-cause mortality. Main secondary outcomes included improvement of KCCQ-TSS (Kansas City Cardiomyopathy Questionnaire and total symptom score) and 6-Minute Walk Test (6MWT). All pooled results were calculated by the random-effects model. Statistical heterogeneity was assessed using the chi-squared test and was quantified using the I-squared statistic. Results Ten RCTs comprising 10,334 patients were involved in. Incidence of composite outcome was reduced in SGLT-2 inhibitor group compared with placebo (HR: 0.78, 95% CI: 0.69–0.88, p = 0.00). Improvement of KCCQ-TSS was also more pronounced in the SGLT-2 inhibitor group (MD: 2.74, 95% CI: 1.30–4.18, p = 0.00). No statistical difference was observed in 6MWT. Conclusion Treating HFpEF patients with SGLT-2 inhibitors is associated with reducing the composite outcome of CV death and HHF and improving health-related quality of life. Further studies with more evidence are in need to confirm this conclusion.